2010
DOI: 10.1097/mpa.0b013e3181c8b48c
|View full text |Cite
|
Sign up to set email alerts
|

Analogs of Vitamin E Epitomized by α-Tocopheryl Succinate for Pancreatic Cancer Treatment

Abstract: Only a minority of PC cells are sensitive to the antiproliferative effects of alpha-TOS, any sensitivity appearing to be correlated with SMAD4/DPC4 homozygous deletion and Bax/Bak expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 39 publications
(43 reference statements)
0
10
1
Order By: Relevance
“…In another recent study, Greco did not show any apoptotic changes until 30-h incubation with 80 lM VES. Greco et al (2010) also observed mild sensitivity to VES at 100 lM concentration, which was close to our apoptotic-inducing concentration in PANC-1 cells (Greco et al 2010). Other than PANC-1, the cell lines used by Greco et al were different than used in our study and might explain the differences in results.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In another recent study, Greco did not show any apoptotic changes until 30-h incubation with 80 lM VES. Greco et al (2010) also observed mild sensitivity to VES at 100 lM concentration, which was close to our apoptotic-inducing concentration in PANC-1 cells (Greco et al 2010). Other than PANC-1, the cell lines used by Greco et al were different than used in our study and might explain the differences in results.…”
Section: Discussioncontrasting
confidence: 53%
“…Earlier studies on the effects of VES on pancreatic cancer cells have reported contradictory results (Greco et al 2010;Heisler et al 2000;Ohlsson et al 2004). Ohlsson et al (2004) found that pancreatic cell lines are insensitive to VES; however, the maximum concentration used in this study was low at 1 lM (Ohlsson et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking into earlier clinical trials on dietary antioxidants in cancer condition, we have not received encouraging results. 47,48 Moreover, NAC treatment leads to the attenuation of apoptotic functions of ROS inducers, further emphasizing toward the optimization of antioxidant therapies against PC. 49 However, due to observed overexpression of HIF-1α even under normoxic condition, current study encourages HIF-1α targeting, which will led to the downregulation of multiple oncogenic proteins, including mucins.…”
Section: Discussionmentioning
confidence: 99%
“…MiaPaCa2, β‐TC6, and HepG2 were cultured in Dulbecco's modified eagle medium (DMEM) (Gibco/BRL) supplemented with 10% (MiaPaCa2 and HepG2) or 15% (β‐TC6) FCS, 2% L ‐glutamine and 0.1% Gentamycin. BxPC3 cells were transfected with the expression vector pBK‐cytomegalovirus (CMV)‐SMAD4/DPC4, as previously described (Greco et al, 2010). One SMAD4/DPC4‐expressing clone (BxPC3‐SMAD4+) was used for S100A8 real time PCR analysis.…”
Section: Methodsmentioning
confidence: 99%